PRODUCTIVITY OF LABOUR IN AGRICULTURAL ENTERPRISES IN SELECTED EU COUNTRIES - Slawomir JARKA (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The objective of the article is to indicate the differences between labour productivity in the Polish agriculture and the EU countries, with special emphasis on the largest producers of food. The article makes use of the data from the Central Statistical Office (GUS) and Eurostat. The difference between the labour productivity in the Polish agriculture and in leading European farms is very significant (German, British or French productivity is 6-7 times higher). The limited growth of labour productivity in agriculture results from endogenous and from exogenous factors.